Spin-Crossover Properties of an Iron(II) Coordination Nanohoop - Heras Ojea, María José; Van Raden, Jeff M.; Louie, Shayan; Collins, Richard; Pividori, Daniel Maximilian; Cirera, Jordi; Meyer, Karsten; Jasti, Ramesh; Layfield, Richard A. (Angewandte Chemie International Edition, 2020)
Addition of the bipyridyl-embedded cycloparaphenylene nanohoop bipy[9]CPP to [FeH2B(pyz)2] (pyz=pyrazolyl) produces the distorted octahedral complex [Fe(bipy[9]CPP)H2B(pyz)22] (1). The molecular structure of 1 shows that the nanohoop ligand contains a non-planar bipy unit. Magnetic susceptibility measurements indicate spin-crossover (SCO) behaviour with a T1/2 of 130 K, lower than that of 160 K observed with the related compound [Fe(bipy)H2B(pyz)22] (2), which contains a conventional bipy ligand. A computational study of 1 and 2 reveals that the curvature of the nanohoop leads to the different SCO properties, suggesting that the SCO behaviour of iron(II) can be tuned by varying the size and diameter of the nanohoop.
CRIS-Team Scopus Importer:2020-12-25
Keywords: iron; magnetic properties; molecular materials; nanohoop ligand; spin crossover